WOMEN IN REPRODUCTIVE SCIENCE: Errors and insight: intentional and accidental studies of human chromosome abnormalities. Issue 6 (December 2019) - Hunt, Patricia A
Abstract : Perhaps every career makes sense in retrospect. I have spent mine facing a series of accidental environmental exposures that derailed our studies but provided new insight. Although at times I have felt more catalyst than scientist, the journey has been extraordinary, and the problem I have spent my career studying – human aneuploidy – has taken on new significance with growing evidence of the sensitivity of the germline to the environment.